Health-Related Quality of Life Among Elderly in Tehran: Urban HEART-1 - Farshad Sharifi; Mehdi Varmaghani; Zahra Sharifi; Fatemeh Leghaei; Nafiseh Zare Kohan; Mohsen Asadi Lari; Reza Fadyevatan (Tehran University of Medical Sciences, 2022)
Background: The aging growth rate is more rapid in developing countries than in more developed countries. This rate is higher in Tehran metropolitan than in most of the other regions of Iran. This study aimed to indicate of disparity and inequity of levels of health related quality of life between different districts of the Tehran metropolitan. Methods: This study analyzed the data of 1890 elderly aged ≥65 years who responded to questionnaires of the Urban-HEART survey. The Persian version of Short-Form Health Survey version 2 (SF 12 v2) was used for the assessment of the health-related quality of life. This instrument has two major components, including Physical Component Summary (PCS) and Mental Component Summary (MCS), and also has eight subscales. The mean of these scores was compared between genders and age groups and districts of the Tehran metropolitan using a one-way Analysis of Variance (ANOVA). Results: Mean±SD age of participants was 73.65±5.91 years. The Mean±SD age in men was 72.97±5.76 years. The Mean±SD PCS score in the participants was 33.36±10.48 and Mean±SD MCS score was 44.26±11.22. The Mean±SD PCS and MCS scores were lower in females than males. The highest Mean±SD PCS scores were observed in district 22 (37.25±11.51) and the lowest Mean±SD PCS scores were observed in district 16 (30.17±9.27). Conclusion: The result of this study help health and urban policymakers could better diagnose and plan for decreasing these inequities in Tehran.